Needs analysis for the personal, social, and psychological adjustment of adolescents at risk of delinquency and juvenile offenders - Mayorga-Sierra, Érika; Novo, Mercedes; Fariña, Francisca; Seijo, Dolores (Anales de Psicología / Annals of Psychology, 2020)
Literature has found that non-criminogenic needs also are a juvenile delinquency risk factor and, consequently, should be target of intervention. With the aim of knowing if individual, social and psychological adjustment differ between juvenile offenders and foster care adolescents with normal adolescents was designed. A total of 450 adolescents (150 juvenile offenders, 150 foster care adolescents, and 150 normal adolescents) were evaluated in individual, social and psychological adjustment. The results showed a significant effect in the individual, social and psychological adjustment for the population factor. Succinctly, juvenile offenders and foster care adolescents displayed a higher individual maladjustment in the personal and family level than normal adolescents, and, additionally, juvenile offenders in the social level. Likewise, juvenile offenders and foster care adolescents exhibited a higher social maladjustment consisting in more social withdrawal, social anxiety/shyness, and leadership than normal adolescents; and juvenile offenders revealed less consideration for others than normal adolescents. In psychological adjustment, juvenile offenders and foster care adolescents reported more obsessive-compulsive, interpersonal sensitivity, depression, hostile, phobic-anxiety, and psychotic symptomology than normal adolescent; and foster care adolescent more somatic, anxiety (generalized) and paranoid symptoms than normal adolescents. The deficits in these needs were quantified as to estimate the magnitude of the intervention. Theoretical and practical implications for intervention of the results are discussed